Are general practitioners characteristics associated with the quality of type 2 diabetes care in general practice? Results from the Norwegian ROSA4 study from 2014. (3rd April 2018) - Tran, Anh Thi; Bakke, Åsne; Berg, Tore J; Gjelsvik, Bjørn; Mdala, Ibrahimu; Nøkleby, Kjersti; Shakil Rai, Anam; Cooper, John G; Claudi, Tor; Løvaas, Karianne; Thue, Geir; Sandberg, Sverre; et al.
Abstract: Objective: To explore the associations between general practitioners (GPs) characteristics such as gender, specialist status, country of birth and country of graduation and the quality of care for patients with type 2 diabetes (T2DM). Design: Cross-sectional survey. Setting and subjects: The 277 GPs provided care for 10082 patients with T2DM in Norway in 2014. The GPs characteristics were self-reported: 55% were male, 68% were specialists in General Practice, 82% born in Norway and 87% had graduated in Western Europe. Of patients, 81% were born in Norway and 8% in South Asia. Data regarding diabetes care were obtained from electronic medical records and manually verified. Main outcome measures: Performance of recommended screening procedures, prescribed medication and level of HbA1c, blood pressure and LDL-cholesterol stratified according to GPs characteristics, adjusted for patient and GP characteristics. Result: Female GPs, specialists, GPs born in Norway and GPs who graduated in Western Europe performed recommended procedures more frequently than their counterparts. Specialists achieved lower mean HbA1c (7.14% vs. 7.25%, p  < 0.01), a larger proportion of their patients achieved good glycaemic control (HbA1c = 6.0%–7.0%) (49.1% vs. 44.4%, p  = 0.018) and lower mean systolic blood pressure (133.0 mmHg vs. 134.7 mmHg, p  < 0.01) compared with non-specialists. GPs who graduated in Western Europe achieved lower diastolic blood pressure than their counterparts (76.6 mmHg vs. 77.8 mmHg, p  < 0.01). Conclusion: Several quality indicators for type 2 diabetes care were better if the GPs were specialists in General Practice. Key Points: Research on associations between General Practitioners (GPs) characteristics and quality of care for patients with type 2 diabetes is limited. Specialists in General Practice performed recommended procedures more frequently, achieved better HbA1c and blood pressure levels than non-specialists. GPs who graduated in Western Europe performed screening procedures more frequently and achieved lower diastolic blood pressure compared with their counterparts. There were few significant differences in the quality of care between GP groups according to their gender and country of birth.